PUBLIC SERVICE QUALITY AND COMMUNITY RETENTION IN ENHANCING PUBLIC SATISFACTION: THE MEDIATING ROLE OF TRUST AT JEMBER POLICE - Agus Yudi Kurniawan; Budi Santoso; Feti Fatimah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
Quality police services are one of the main factors in building public trust and satisfaction with the police institution. However, there are still challenges in improving the quality of service and effective community retention as a form of support and loyalty to the Jember Police. This study aims to examine the influence of service quality and community retention on community satisfaction in the Jember Regional Police with the role of intervening in public trust. The research method used a quantitative approach by collecting questionnaire distribution data and then in Structural Equation Modeling (SEM) analysis with the WarpPLS statistical tool. The results of the analysis showed that the quality of service and community retention had a positive and significant influence on community satisfaction, both directly and through trust interventions. Trust has proven to be an important mechanism that strengthens the relationship between service quality and retention to community satisfaction. This finding provides strategic implications for the Jember Regional Police to continue to improve the quality and retention of services as an effort to build and maintain public trust in order to increase satisfaction and loyalty of service users. This research also opens up opportunities for the development of a more responsive and reliable public service system in police institutions.